2004
DOI: 10.1016/j.cub.2004.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism for Sensing Noise Damage in the Inner Ear

Abstract: Our sense of hearing requires functional sensory hair cells. Throughout life those hair cells are subjected to various traumas, the most common being loud sound. The primary effect of acoustic trauma is manifested as damage to the delicate mechanosensory apparatus of the hair cell stereocilia. This may eventually lead to hair cell death and irreversible deafness. Little is known about the way in which noxious sound stimuli affect individual cellular components of the auditory sensory epithelium. However, studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
165
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 130 publications
(185 citation statements)
references
References 16 publications
20
165
0
Order By: Relevance
“…This phenomenon could be blocked by extracellular apyrase-which hydrolyses ATP, and the PLC inhibitor U73122. The findings, including block of the Ca 2+ wave propagation using carbenoxolone, a gap junction blocker, suggested that the connexin hemichannel conduit for the ATP release in the cochlea [7,37] is coupled to P2Y receptor signaling [3]. Our data showing prominent P2Y2 receptor expression at this site is consistent with the initial immunolocalization of P2Y 2 to the Hensen's cell region by Gale et al [3].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This phenomenon could be blocked by extracellular apyrase-which hydrolyses ATP, and the PLC inhibitor U73122. The findings, including block of the Ca 2+ wave propagation using carbenoxolone, a gap junction blocker, suggested that the connexin hemichannel conduit for the ATP release in the cochlea [7,37] is coupled to P2Y receptor signaling [3]. Our data showing prominent P2Y2 receptor expression at this site is consistent with the initial immunolocalization of P2Y 2 to the Hensen's cell region by Gale et al [3].…”
Section: Discussionsupporting
confidence: 90%
“…With the exception of P2Y 12 , expression of all these receptors has previously been confirmed in rat cochlear tissues by RT-PCR [3,26]. We complemented this in the present study by confirming P2Y12 transcript expression by RT-PCR alongside immunolocalisation of the five P2Y proteins.…”
Section: Rt-pcr Detection Of P2y12 Receptor Mrna Transcriptsupporting
confidence: 83%
See 3 more Smart Citations